Generation of hiPSC lines with fusion tagged thyroid hormone receptor α isoforms to study isoform-specific actions of TRα1 and TRα2 - Nina Härting; Katarzyna A. Ludwik; Regina Jahn; Frank J. Kaiser; Harald Stachelscheid (Stem Cell Research)
The role of the nuclear thyroid hormone receptor TRα1 as a mediator of thyroid hormone action on target gene expression is well understood. However, the function of the TRα2 splicing isoform, which does not bind thyroid hormones, remains unexplored. As no reliable antibodies are available to investigate TRα1 and TRα2 specifically, we introduced small fusion tags into the THRA locus of the male healthy donor iPSC lines BIHi001-B and BIHi005-A by CRISPR/Cas9-mediated genome editing. Consequently, the modified lines express C-terminally tagged TRα1-2xHA or TRα2-3xFLAG. These genome-edited lines facilitate the investigation of isoform-specific actions of TRα in different cell types.